2015
DOI: 10.1161/jaha.114.001652
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 Metabolizer Status and Clopidogrel Efficacy in the Secondary Prevention of Small Subcortical Strokes (SPS3) Study

Abstract: BackgroundThe role of the CYP2C19 genotype on clopidogrel efficacy has been studied widely, with data suggesting reduced clopidogrel efficacy in loss-of-function variant carriers taking clopidogrel after percutaneous coronary intervention; however, data are limited regarding the association between CYP2C19 genetic variants and outcomes in stroke patients. We investigated whether CYP2C19 metabolizer status affects the risk of recurrent stroke or major bleeding in subcortical stroke patients taking dual antiplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 52 publications
2
46
0
Order By: Relevance
“…No association between bleeding and carrier status was observed in either of the 2 studies. 23,24 The results from the clopidogrel-aspirin-treated group support both of their findings. Jia and colleagues 22 and Yang and colleagues.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…No association between bleeding and carrier status was observed in either of the 2 studies. 23,24 The results from the clopidogrel-aspirin-treated group support both of their findings. Jia and colleagues 22 and Yang and colleagues.…”
Section: Discussionsupporting
confidence: 64%
“…[22][23][24] In a group of 176 white patients with small subcortical stroke who received clopidogrel and aspirin, CYP2C19*2 loss-of-function allele was associated with increased risk of stroke compared with extensive or ultrarapid (*17) metabolizer phenotypes. 23 No such association was observed in either African American or Spanish patients. Sun and colleagues 2 4 observed an increased risk of a composite of vascular events (including vascular death, nonfatal ischemic stroke, and nonfatal myocardial infarction) during 3-month follow-up in carriers compared with noncarriers of CYP2C19*2 or CYP2C19*3 alleles in a cohort of 625 consecutive patients with ischemic stroke receiving clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients included in the analysis were Chinese and only 386 patients (8% of the total 4,762) were of white origin and of these over 90% were from two studies using dual antiplatelet therapy. 22,24 Interestingly, the risk of vascular endpoints in relation to CYP2C19 genotype seems to be lower in studies in which the study protocol clearly included dual antiplatelet therapy for 90 days or longer than in studies using clopidogrel monotherapy. 13 Indeed, excluding the small number of individuals who were co-prescribed aspirin in our study further increased the HR (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that carriers with CYP2C19 alleles *2 or *3 had significantly lower levels of the active metabolite of clopidogrel, and could be considered as risk predictors for clinical outcomes in ACS or patients with cerebrovascular ischemic stroke. McDonough et al 16 found that CYP2C19 IMs or PMs had higher residual platelet reactivity than EMs or UMs (ultrarapid metabolizers) during the follow-up period. Wallentin et al 17 also reported that carriers of the reduced function CYP2C19 allele variants showed a higher rate of clopidogrel resistance, and the occurrence of cardiovascular death, myocardial infarction or stroke, mainly within the first 30 days after the treatment for ACS.…”
Section: Discussionmentioning
confidence: 99%